1996
DOI: 10.1046/j.1365-2796.1996.30295851000.x
|View full text |Cite
|
Sign up to set email alerts
|

Population‐based erythrocyte sedimentation rates in 3910 subjectively healthy Norwegian adults. A statistical study based on men and women from the Oslo area

Abstract: The upper reference levels expected to be exceeded only by chance in 5% of single individual recordings at the ages of 20, 55 or 90 years, respectively, were estimated to be 12, 14 and 19 mm h-1 for men, and 18, 21 and 23 mm h-1 for women. Higher values should be controlled and, if confirmed, lead to a clinical check-up. However, about 76% of our overall material had ESR values lower than 9 mm h-1. Knowledge of each person's baseline ESR value might increase the disease-predictive ability of the test. If sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1
4

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 9 publications
1
36
1
4
Order By: Relevance
“…The test measures the distance erythrocytes fall after an hour in a vertical column of anticoagulated blood under the influence of gravity (Saadeh, 1998). The basic factors influencing the ESR have been understood since the early part of this century; the amount of fibrinogen in the blood directly correlates with the ESR (Wetteland et al, 1996). There are two main methods of performing the ESR; the Wintrobe and Westergren method (Lewis et al, 2006).…”
mentioning
confidence: 99%
“…The test measures the distance erythrocytes fall after an hour in a vertical column of anticoagulated blood under the influence of gravity (Saadeh, 1998). The basic factors influencing the ESR have been understood since the early part of this century; the amount of fibrinogen in the blood directly correlates with the ESR (Wetteland et al, 1996). There are two main methods of performing the ESR; the Wintrobe and Westergren method (Lewis et al, 2006).…”
mentioning
confidence: 99%
“…A population study of 3,910 healthy Norwegian adults found that the upper reference levels expected to be exceeded by chance 5% of the time were 19 mm h -1 for men and 23 mm h -1 for women over the age of 90 years [18]. Using that criterion, all but 1 patient in our series would have had an elevated ESR.…”
Section: Discussionmentioning
confidence: 83%
“…The order of theoretical sedimentation rate agrees with that from other clinical reports. 5,44,45 In our design, the height of the separation chamber (H ch ) is around 80 lm, which will take roughly 100 s for all the RBCs to settle down near the bottom of the separation chamber (t s % 100 s). The flow rate of all the devices in case I was kept the same (Q % 2.5 nl/s), and the volume of the separation chamber (V s ) is around 10 9 lm 3 .…”
Section: Blood Sedimentationmentioning
confidence: 99%